2004
DOI: 10.1097/01.ju.0000143549.29867.4e
|View full text |Cite
|
Sign up to set email alerts
|

Cyclophosphamide Induced Cystitis Alters Neurotrophin and Receptor Tyrosine Kinase Expression in Pelvic Ganglia and Bladder

Abstract: Cystitis decreases bladder NGF and BDNF expression, whereas MPG expression is increased. This change may reflect neurotrophin release at the bladder and retrograde transport to the MPG. TrkA-IR and TrkB-IR are increased in bladder postganglionic cells and bladders with cystitis. This increase may reflect a shift in Trk staining from urothelium to detrusor muscle and nerve fibers with cystitis. Neurotrophin/Trk interactions in the bladder and MPG may contribute to bladder overactivity with cystitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
87
1
6

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 87 publications
(101 citation statements)
references
References 21 publications
7
87
1
6
Order By: Relevance
“…As previously described (Vizzard, 2000c;Murray et al, 2004), tissue was homogenized and centrifuged (10,000 rpm for 5 min); supernatants were used for NGF quantification. Total protein was determined (Pierce).…”
Section: Enzyme-linked Immunoassays For Ngf In Urinary Bladdermentioning
confidence: 99%
“…As previously described (Vizzard, 2000c;Murray et al, 2004), tissue was homogenized and centrifuged (10,000 rpm for 5 min); supernatants were used for NGF quantification. Total protein was determined (Pierce).…”
Section: Enzyme-linked Immunoassays For Ngf In Urinary Bladdermentioning
confidence: 99%
“…A possible explanation relies on the following observations: (1) Although in the neuronal system, high concentrations of mature NTs required to induce even modest levels of apoptosis are considered non-physiological, 34 in human epidermis, the NT-4, BDNF or other yet unidentified ligands could autocrinally and paracrinally be continuously released and in turn bind p75NTR, thus overcoming Trk functions. (2) Epithelial cells behave differently from neurons, as normal prostate and bladder cells express Trk 35,36 and still undergo apoptosis via p75NTR binding. 37 It has been recently shown that, under certain circumstances and stimuli, a Trk-to-p75NTR molecular switch occurs favoring cell death.…”
mentioning
confidence: 99%
“…NGFand BDNF-IRs have been previously found by using ELISA in the MPG ganglia of male rats (Murray et al 2004). Moreover, TrkA-, TrkB-and p75 NTR -IRs have been found by using immunohistochemistry in the majority of neurons of these ganglia (Keast and Kepper, 2001;Murray et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been observed that NGF, BDNF and TrkB were expressed in major pelvic ganglion neurons and their expression increased after cyclophosphamide-induced cystitis in rats (Murray et al 2004).…”
Section: ©2008 European Journal Of Histochemistrymentioning
confidence: 99%